SWOT Analysis of Digitalization Implementation in Verification Processes on the Effectiveness of Financial Management in Tojo Una-Una Regency - Nasrun Naida; Rismanto (ARTOKULO : Journal of Accounting, Economic and Management, 2024)
This study evaluates the impact of digitalization of the verification process on the effectiveness of financial management using a SWOT analysis. A qualitative descriptive method involving case studies, in-depth interviews, participatory observation, and documentation was employed to explore the strengths, weaknesses, opportunities, and threats of implementing a digital system. The results indicate that the "aksi-BPKAD" innovation can accelerate processes, and enhance transparency and accountability in regional financial management. implementing these recommendations, it is hoped that the "aksi-BPKAD" innovation can be fully optimized to improve regional financial management in Tojo Una-Una Regency